HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM DI PUSKESMAS SELAT BARU KECAMATAN BANTAN KABUPATEN BENGKALIS - Susanti, Susanti; Ruspita, Rika; Susanti, Komaria; Mardiya, Rizka (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Hyperemesis gravidarum is vomiting that occurs in early pregnancy until 20 weeks of gestation. The World Health Organization (WHO, 2021) reports that the incidence of hyperemesis gravidarum reaches 12.5% of all pregnancies in the world. The aim of the research is to determine the relationship between knowledge and attitudes of pregnant women and the incidence of Hyperemesis Gravidarum at the Selatbaru Community Health Center, Bantan District, Bengkalis Regency. This type of research is descriptive correlational with a cross sectional approach. The population in this study were all pregnant women at the Selatbaru Community Health Center based on KIA reports for January - November 2024, totaling 129 KEK pregnant women. The sampling method was using the Accidental sampling technique, totaling 97 respondents. The data collection process uses a questionnaire. Data analysis used the Chi-Square Test with a confidence level of 95%. Research results: the majority of respondents have less knowledge about the incidence of hyperemesis gravidarum (53.6%), the majority of respondents have a negative attitude towards the incidence of hyperemesis gravidarum (53.6%), there is a relationship between knowledge and the incidence of CED with a value of ρ=0.000 and there is a relationship attitude of pregnant women with the incidence of CED with a value of ρ=0.025. The conclusion is that there is a relationship between the knowledge and attitudes of pregnant women and the incidence of Hyperemesis Gravidarum at the Selatbaru Community Health Center, Bantan District, Bengkalis Regency. Suggestions for pregnant women to be more active in seeking information about hyperemesis gravidarum and health information during pregnancy both through the media, environment and health education, posyandu activities so that pregnant women's knowledge about health during pregnancy, especially knowledge about hyperemesis gravidarum, can increase so that pregnant women can respond to it. with nausea and vomiting that may occur in pregnancy.Keywords: Knowledge, Attitudes, Hyperemesis Gravidarum